ASSESSMENT OF THE FISH-WEIR FISHERY OFF THE COAST OF PIAUÍ STATE, BRAZIL - Mai, Ana Cecília Giacometti; Silva, Thiago Fernandes A.; Legat, Jefferson Francisco A. (Arquivos de Ciências do Mar, 2012)
Fish-weirs are stationary traps set up by fishermen in places with a considerable tidal height variation. This work followed the harvesting of three fish-weirs off the coast of Piauí State, Brazil. Sampling was conducted at daytime and nighttime shifts, during six days of each month of the period from December. 2008 through November, 2009. A total of 117 fish species was registered, belonging to 41 families. There was no significant difference in mean catch weight between the dry and wet seasons, the daytime and nighttime shifts, and full moon and new moon phases. The annual catch per fish-weir was estimated as 1.2 ton, of which 79.0% were made up of commercially-important fish species for Piauí State.